2012
DOI: 10.3121/cmr.2012.1105
|View full text |Cite
|
Sign up to set email alerts
|

ADAMTS13 Deficiency and Thrombotic Thrombocytopenic Purpura Associated with Trimethoprim-Sulfamethoxazole

Abstract: Case PresentationA previously healthy woman, age 26 years, presented with abdominal pain, progressive fatigue, and purpuric skin rash over the extremities that began 7 days after beginning a treatment with trimethoprim-sulfamethoxazole (TMP-SMX) for a Klebsiella pneumoniae urinary tract infection. She also complained of exertional shortness of breath with no cough, hemoptysis, or other cardiopulmonary symptoms. No history of bleeding gums or hematochezia was present. A detailed interrogation did not demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
(37 reference statements)
0
3
1
Order By: Relevance
“…Changes in hematological parameters observed in rats treated with SMX/TMP are in agreement with some observations. 15,16 Mallolas et al, 17 in their study reported some cases of LPV/r associated impairments in hematological function which disagrees with observations in this study. 18 Concurrent use of these agents may not have any deleterious effects on hematologic parameters as observed in this study.…”
Section: Discussioncontrasting
confidence: 57%
“…Changes in hematological parameters observed in rats treated with SMX/TMP are in agreement with some observations. 15,16 Mallolas et al, 17 in their study reported some cases of LPV/r associated impairments in hematological function which disagrees with observations in this study. 18 Concurrent use of these agents may not have any deleterious effects on hematologic parameters as observed in this study.…”
Section: Discussioncontrasting
confidence: 57%
“…TTP has diverse etiologies, including cancer, infection, stem cell transplantation, organ transplantation, and medication such as chemotherapy. Drug-related TTP is common and represents 12% of cases [ 7 ]. TTP can be divided into hereditary and acquired.…”
Section: Discussionmentioning
confidence: 99%
“…TTP has diverse etiologies including infections, medications, and idiopathic and familial causes. Drug-associated TTP represents about 12% of all cases [ 9 ]. Before the advent of plasma therapy, most of the patients presenting with acute TTP died: the case-fatality rate reported in clinical series was near 100% until the 1960s [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%